Influence of Electrolyte Molarity and Applied Voltage on the Purification of Ferronickel by Electrolysis Method - Astini, Vita; Meirawati, Selvia; Nengsih, Sulistia; -, Arif; -, Hasriyanti; Soedarsono, Johny Wahyuadi Mudaryoto; Zulfia, Anne (Metalurgi, 2024)
The current advancements in the automotive industry highlight the critical need for electric vehicles, which require a reliable supply of nickel for battery production. A potential nickel source is Ferronickel's local content, which can be used as a secondary resource. However, research on converting smelted Ferronickel into electrolytic nickel is still limited. This study aims to examine the effects of electrolyte molarity and applied voltage during the electrolysis process for refining Ferronickel. The molarities of HCl employed in this research are 0.1, 0.25, 0.5, 0.75, and 1 M for 2 hours. Additionally, the molarities of HCl are set at 2, 3, and 4 M for 6 hours. Further experiments were performed using varying voltages of 1, 2, 4, 6, and 8 V while keeping the solution concentration constant at 1 M and maintaining an electrolysis duration of 2 hours. The electrolysis solution was subsequently analyzed using the AAS (atomic absorption spectrophotometry) test. The results indicated that higher molarity levels were associated with increased current, resulting in faster reaction rates and greater solubilization of nickel metal. The Ni concentration rose with higher molarity, increasing from 76.50 mg/L in .25 M HCl to 91.88 mg/L in 1 M HCl. In contrast, the Fe concentration remained nearly constant across various molarity levels, ranging from 11.81 mg/L in .25 M HCl to 11.95 mg/L in 1 M HCl, suggesting a minimal influence of molarity below 1 M. Fe exhibited a strong positive correlation with increasing electrolyte molarity, showing a significant rise in concentration from 49.06 g/L at 2 M to 90.17 g/L at 4 M. Ni showed a more modest response to elevated molarity, with concentrations increasing from 11.95 g/L at 2 M to 22.70 g/L at 4 M. The Ni concentration increased with the applied voltage up to 6 V, reaching 95.57 mg/L, but then decreased to 77.67 mg/L at 8 V, indicating that the optimum voltage is 6 V. The Fe concentration displayed slight fluctuations but remained relatively stable across different voltage levels, measuring 11.81 mg/L at 1 V and 12.28 mg/L at 8 V, indicating that the applied voltage does not significantly influence Fe concentration in the solution.